Growth performance and carcass quality of Tre chickens raised in different levels of saline water - Nguyen Thuy Linh; Nguyen Hoang Qui; Nguyen Thi Truc Linh; Nguyen Van Vui; Truong Thanh Trung; Nguyen Thi Kim Dong (Veterinary Integrative Sciences)
This study aimed to find the effect of saline water on the growth performance and carcass characteristics of Tre chickens. A total of 150 Tre chickens was allotted in five treatments and three replicates per treatment. A completely randomized design was used for this study in which the birds from 4-14 weeks old had ad libitum access to feed and water in all treatments with five levels of salt (0, 0.2, 0.4, 0.6, and 0.8%). The results showed that the growth performance of Tre chicken was decreased when increased levels of salt in drinking water (P<0.05). The birds avoided drinking water from treatment with salt of 0.8% (P<0.05). The feed conversion ratio of birds was lowest at the treatment of 0 and 0.2%. Besides, carcass traits (carcass, breast, thigh, and gizzard weight) were decreased significantly when the level of salt in drinking water increased over 0.2% (P<0.05), but there were no significant differences between 0-0.2% salt in drinking water (P>0.05). Small intestine weight was longer at control treatment while large intestine was longer at treatment of 0.2% salt. Additionally, all examined criteria were decreased significantly with 0.4, 0.6, and 0.8% of salt in drinking water (P<0.05). It can be concluded that Tre chickens’ growth could tolerant the salinity in drinking water up to 0.2%. With over 0.2% salt in drinking water, chicken’s performance might be reduced.